Attraction of the Indian Meal Moth Plodia interpunctella (Lepidoptera: Pyralidae) to Commercially Available Vegetable Oils: Implications in Integrated Pest Management - Liu J; Yu Z; He XZ; Zhou G; Guo M; Deng J (Massey University, 2024)
The Indian meal moth, Plodia interpunctella, poses a significant threat to global agricultural products. Although pheromone-based technologies show promise for P. interpunctella management, limitations such as single-sex targeting necessitate exploring complementary strategies. Vegetable- based oils represent a potential alternative but their efficacy, sex-specificity, and interaction with sex pheromones remain unclear. To address these questions, we first examined the attraction of P. interpunctella female and male adults to 10 commercially available vegetable oils in semi-field conditions. Sesame, olive, and blended oils were the most attractive, capturing significantly more adults compared to other oils. We then evaluated the effectiveness of these three attractive oils and their combinations with P. interpunctella sex pheromones in a grain warehouse. Traps baited with these oils captured significantly more females and males compared to control traps without attractants; however, the addition of sex pheromones did not improve male capture and significantly reduced female capture, suggesting an inhibitory effect. Finally, we demonstrated that female mating status (mated vs. virgin) did not influence the attractiveness of traps baited with these effective oils. Our findings highlight the potential of standalone traps baited with blended, olive, or sesame oil as a practical, economic, and effective management strategy for P. interpunctella in storage facilities.